Dialektis Gademer - Damanik, Nurliana (UIN Sumatera Utara, 2023)
Hans-Georg Gadamer is one of the thinkers who falls into the group of ontological hermeneutics. Gadamer matured the idea of consciousness, interpretation of texts and phenomena and discovered the philosophical problem of developing an ontology of understanding objectively in progress. Hermeneutics is always related to language. Gadamer stated that language is the modus operandi of humans' way of being in the world and a form that seems to embrace the entire constitution of the world. For Gadamer, language is time, human existence, being, and truth. Mastery of a language and its unique set of experiences and traditions is the main requirement for the disclosure of ontology itself. The important point of Gadamer's hermeneutic theory refers to the hermeneutic circle regarding dialectical understanding. Dialectical understanding is a process of historical awareness, born due to the involvement of the dimensions of time, namely past, present and future. Truth is achieved when there is a fusion of the horizons of the text, actors and interpreters (fusion horizon). In this understanding, the involvement of language becomes very important. Interpretation is not just reproductive work but rather productive understanding, giving birth to new interpretations and meanings. Gadamer formulated two forms of understanding, namely understanding the truth content and understanding the intention. Understanding content means understanding the meaning contained in the propositions and substance of the text material. Understanding intention means understanding the conditions or situations behind a phenomenon or text. Understanding this second aspect then became Gadamer's attention as an awareness of historical understanding. Historical understanding is obtained through the proposition of historicity, where the awareness of the subject (text interpreter) in carrying out analysis (text interpretation) is required to be inseparable from the study of historical experiences related to the text. Understanding the text is understanding history with the principles of space and time).Keywords: Gademer, Dialectics, Hermeneutics, Understanding.